Longitudinal study of muscle strength, quality, and adipose tissue infiltration - Delmonico, Matthew J; Harris, Tamara B; Visser, Marjolein; Park, Seok Won; Conroy, Molly B; Velasquez-Mieyer, Pedro; Boudreau, Robert; Manini, Todd M; Nevitt, Michael; Newman, Anne B; Goodpaster, Bret H (The American journal of clinical nutrition, 2009)
Sarcopenia is thought to be accompanied by increased muscle fat infiltration. However, no longitudinal studies have examined concomitant changes in muscle mass, strength, or fat infiltration in older adults. We present longitudinal data on age-related changes in leg composition, strength, and muscle quality (MQ) in ambulatory, well-functioning men and women. We hypothesized that muscle cross-sectional area (CSA) and strength would decrease and muscular fat infiltration would increase over 5 y. Midthigh muscle, subcutaneous fat (SF), and intermuscular fat (IMF) CSAs and isokinetic leg muscle torque (MT) and MQ (MT/quadriceps CSA) were examined over 5 y in the Health, Aging, and Body Composition study cohort (n = 1678). Men experienced a 16.1% loss of MT, whereas women experienced a 13.4% loss. Adjusted annualized decreases in MT were 2-5 times greater than the loss of muscle CSA in those who lost weight and in those who remained weight-stable. Weight gain did not prevent the loss of MT, despite a small increase in muscle CSA. Only those who gained weight had an increase in SF (P < 0.001), whereas those who lost weight also lost SF (P < 0.001). There was an age-related increase in IMF in men and women (P < 0.001), and IMF increased in those who lost weight, gained weight, or remained weight-stable (all P < 0.001). Loss of leg MT in older adults is greater than muscle CSA loss, which suggests a decrease in MQ. Additionally, aging is associated with an increase in IMF regardless of changes in weight or SF.